Evaluation of Reinforced Concrete Structural Design of the Bengkalis State Polytechnic Rectorate Building against Vertical Load Performance Based on Indonesian National Standards (SNI) - Arizona Arifin; Febriko Husaini (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
This study evaluates the reinforced concrete (RC) structural design of the Bengkalis State Polytechnic Rectorate Building, with a particular focus on its performance under vertical loads an aspect that has been rarely addressed for educational buildings in Indonesia. Structural analysis was conducted based on Indonesian National Standards (SNI 1727:2020, SNI 2847:2019, and SNI 1726:2019). Dead and live loads were determined according to building functions, and the factored load combination (1.2DL + 1.6LL) was applied. The total design vertical load was found to be approximately 12,255 kN. Verification of structural members demonstrated that all reinforced concrete elements including beams, columns, and slabs satisfied both ultimate strength and serviceability requirements, with demand-to-capacity ratios (DCR) well below unity. Columns showed significant reserve strength, while beams and slabs met flexural and deflection criteria. These results confirm that the RC structural design of the rectorate building is safe and reliable under vertical loading conditions. The study contributes to the limited literature on vertical load assessment for Indonesian educational facilities and recommends that future research include seismic and lateral load analysis due to the country’s high seismicity.